The Handbook of children, media, and development - Calvert, Sandra L.; Wilson, Barbara J. (Wiley-Blackwell, 2011)
Media use starts in the first year of life. Initial experiences are controlled by parents and caregivers, but increasingly give way to childrena s preferences. The degree to which these experiences are a positive or negative source of developmental change is an ongoing intellectual debate with significant implications for today's society.